Emergency Management of Diverticulitis - Bauer, Valerie P. (Thieme Medical Publishers, 2009)
The most common indications for emergency operative intervention in the treatment of sigmoid diverticulitis are peritonitis and failure of medical therapy. Primary resection and diversion (Hartmann's procedure) followed by delayed colostomy closure is the current standard of emergency surgical care. Guidelines for best operative strategy, however, remain controversial and continue to evolve based on recent comparative reviews of surgical outcomes. Primary resection and anastomosis with or without proximal diversion and laparoscopic lavage are alternatives to Hartmann's procedure that may provide an improved outcome in properly selected patients. Ongoing changes in the historical paradigm of the surgical approach to this disease mandate the need for large multicentered prospective randomized trials to determine the best surgical strategy under emergent conditions for the treatment of diverticulitis. The current literature is reviewed with suggestions for a management algorithm.